The optimal inflation tax when taxes are costly to collect - Fiorella De Fiore (European Central Bank (ECB), 2000)
Tax collection costs have been advocated in the literature as a reason to deviate from the Friedman rule, in standard general equilibrium monetary models with flexible prices. This paper shows that there are conditions under which the Friedman rule is optimal despite the presence of collection costs. When these conditions are not satisfied, the optimal inflation tax depends upon the collection costs parameter and schedule, the interest and scale elasticity of money demand, and the compensated labor supply elasticity. Numerical results obtained by calibrating the model on US data suggest that collection costs do not justify substantial departures from Friedman's prescriptions.
Keywords: E31; E41; E58; E62; 330